2014
DOI: 10.1186/1471-2458-14-803
|View full text |Cite
|
Sign up to set email alerts
|

A repeated measurement study investigating the impact of school outdoor environment upon physical activity across ages and seasons in Swedish second, fifth and eighth graders

Abstract: BackgroundSchool children are confined to and exposed to outdoor environment that happens to be at their disposal during compulsory school time. The health-promoting potential of outdoor environment, and the use of it, is therefore important. We have studied the impact of school outdoor environment in terms of playground features, space, topography and vegetation upon the patterns of moderate to vigorous physical activity (MVPA) across ages and seasons in Swedish pupils at compulsory school.MethodsFour schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 44 publications
6
52
1
3
Order By: Relevance
“…However, only 4 of these articles [13][14][15][16] were included in this report card since the other 39 articles did not provide any estimates of the percentage of children and adolescents meeting the PA recommendations. In total, 4 studies objectively measured MVPA [13][14][15][16] and 1 subjectively measured SB (screen time; ie, TV/DVD/video viewing) 13 in relation to the recommendations. The amount of children reaching the recommendation for overall PA was assessed via those who fulfilled the recommendations of greater than 60 minutes of MVPA in accordance with the NNR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only 4 of these articles [13][14][15][16] were included in this report card since the other 39 articles did not provide any estimates of the percentage of children and adolescents meeting the PA recommendations. In total, 4 studies objectively measured MVPA [13][14][15][16] and 1 subjectively measured SB (screen time; ie, TV/DVD/video viewing) 13 in relation to the recommendations. The amount of children reaching the recommendation for overall PA was assessed via those who fulfilled the recommendations of greater than 60 minutes of MVPA in accordance with the NNR.…”
Section: Methodsmentioning
confidence: 99%
“…13 Three older reports in this age group used lower cut-points for MVPA and reported that as many as 93% to 100% of 8-to 11-year-old children (boys and girls) fulfilled the recommendation. [14][15][16] For adolescents, 10% and 15% of 13-and 15-year-olds reached the allotted 60 minutes. 23 …”
Section: Variables and Their Contribution To Pa Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This shift may in part be due to the availability of electronic media in the home and parental restrictions regarding engaging in informal and unsupervised activity outdoors (Karsten, 2005; Tandy, 1999). As children grow older they spend less time outdoors (Cleland et al, 2010; Pagels et al, 2014). One study found that over a 5-year period among initially 10–11 year old children, time spent outdoors decreased by 31% in girls and by 19% in boys (Cleland et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This study is like studies in medicine and educational science, where the fundamental is that each individual is involved with only one of alternative cure or environments (Keselman et al 2001;Singh et al 2013;Pagels et al 2014). In this study the system corresponds to a cure or environment.…”
Section: Discussionmentioning
confidence: 99%